The adaptation of the Postpartum-Specific Anxiety Scale into the Turkish language - BAYRI BİNGÖL, FADİME; DEMİRGÖZ BAL, MELTEM; ZENGİN, ORHAN (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
Background: The Postpartum Specific Anxiety Scale (PSAS) is used as a descriptive instrument to measure anxiety. Aim: The aim of this study was to examine the validity and reliability of the Turkish version of the PSAS. Study Design: The study is of methodological design. Methods: The study was conducted with 360 women who had given birth four months ago and presented at a Family Health Center. The validity analysis of the data was performed using the content validity index, exploratory factor analysis, confirmatory factor analysis, reliability analysis, Pearson's Moments Multiplication Correlation and Cronbach's Alpha Coefficient of Reliability. Correlation analysis, Cronbach's alpha analysis, and exploratory/confirmatory factor analysis were used in the evaluation of the data. Results: To assess the consistency of the scale over time, test-retest measurements were taken in a two-week interval. In the analysis of the internal consistency of the PSAS, Cronbach's alpha coefficient of reliability was .90 for maternal competence and attachment anxieties, .89 for infant safety and welfare anxieties, .83 for practical infant care anxieties, .83 for psychosocial adjustment to motherhood, and .94 for the overall scale. Conclusion: Our study has demonstrated that the Turkish version of the scale is a valid and reliable tool to use.
Keywords: Postpartum Specific Anxiety Scale; validity; reliability; postpartum; anxiety; DEPRESSION